TINGKAT KESADARAN PENDUDUK NONPERMANEN TERHADAP PENTINGNYA PENCATATAN PENDUDUK NONPERMANEN - Rizda Ardyati; Rakai Zidan Irada (Sekolah Tinggi Pariwisata Mataram, 2022)
This study intend to discover how to raise the awareness of Non-Permanent resident in Department of Population and Civil Registration District Kendal. Non-Permanent resident is Indonesian citizens who live outside the District/City where the permanent residence is different with the address on they e-KTP, and does not intend to move permanently. This study using type of empirical reseach with descriptive qualitative research methods. Sources of data used are primary data sources and secondary data. Primary data obtained from interviews, observations, and documentation. The main resource persons in this study were the Head of the Bidang Pendaftaran Penduduk (DAFDUK) Department of Population and Civil Registration District Kendal and data utilization of Department of Population and Civil Registration District Kendal, also the publics especially Non-Permanent resident. There are 3 stages of data analysis in this study, data reduction, data presentation and conclusion drawing and verification. The results of this study it is known that there is still a lack of awareness from the District Kendal Population to do registration of Non-Permanent Resident which has been running since 2021 and has been in based on PERMENDAGRI Number 14 Of 2015 about Resgistration Of Non-Permanent Resident. This is because there is still lack of understanding from Penduduk Non-Permanent Resident about Registration Of Non-Permanent Resident and still lack socialization about Non-Permanent Resident. Efforts that can be made such as socializing, cooperation, innovation, and utilization of social media.